Language : The social construction of identity in Creole situations / Marcyliena Morgan - Morgan, Marcyliena (Estados Unidos de America : Center of Afro-American Studies UCLA, 1994)
Problems of standardization of creole languages, language estandarization and linguistc fragmentation in tok pisin, sociolinguistic approaches to languag use in the anglophone caribbean, on decreolization, the case of guilah, language and education in Hawai I, sociolopitical and economic implications of hawai´I creole inglish, the african-american speech community, reality and socioligunguist
Index, reference, about the contributors
Col. Soc
Keywords: 1. CLASES SOCIALES 2. LANGUAGE 3. SOCIAL CONSTRUCTION-IDENTITY 4. CREOLE SITUATIONS 5. SOCIOLOGY